The Functioning of Coal Mining in a Knowledge-Based Economy - Heder, Arkadiusz; Tkocz, Maria (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Abstract: Coal mining, due to its restructuring, has recently been achieving positive financial results.Currently, it is facing the challenge of international competitiveness, particularly because Poland is thelargest coal producer in the European Union, which comprises only 1.1% of the world’s production(2011). One of the great chances for its further development is the implementation of principles ofa knowledge-based economy aimed at generating innovative ideas, which, once implemented, bring material or social profits. According to OECD’s definition, a knowledge-based economy (KBE) isaimed at creating, understood as production, and further transmitting, that is distribution, as well aspractical applications of knowledge and information. According to A. Kuklinski (2001), KBE is basedon four basic pillars. The first pillar is education and training. The second pillar is information infrastructure.The third pillar is economic conditionings and institutional conditions, while the fourth areinnovation systems.The question that presents itself is whether the above rudiments of a knowledge-based economy arebeing implemented in coal mining in Poland. The article attempts to answer the question. It presents diversifiedforms of cooperation with academic and research units as well as business-related institutions.